Direct costs of overdiagnosed asthma: a longitudinal, population-based cohort study in British Columbia, Canada. Issue 11 (7th November 2019) - Ng, Bryan; Sadatsafavi, Mohsen; Safari, Abdollah; FitzGerald, J Mark; Johnson, Kate M
Abstract : Objectives: A current diagnosis of asthma cannot be objectively confirmed in many patients with physician-diagnosed asthma. Estimates of resource use in overdiagnosed cases of asthma are necessary to measure the burden of overdiagnosis and to evaluate strategies to reduce this burden. We assessed differences in asthma-related healthcare resource use between patients with a confirmed asthma diagnosis and those with asthma ruled out. Design: Population-based, prospective cohort study. Setting: Participants were recruited through random-digit dialling of both landlines and mobile phones in the province of British Columbia, Canada. Participants: We included 345 individuals ≥12 years of age with a self-reported physician diagnosis of asthma. The diagnosis of asthma was reassessed at the end of 12 months of follow-up using a structured algorithm, which included a bronchodilator reversibility test, methacholine challenge test, and if necessary medication tapering and a second methacholine challenge test. Primary and secondary outcome measures: Self-reported annual asthma-related direct healthcare costs (2017 Canadian dollars), outpatient physician visits and medication use from the perspective of the Canadian healthcare system. Results: Asthma was ruled out in 86 (24.9%) participants. The average annual asthma-related direct healthcare costs for participants with confirmed asthma were C497.9 (SD C677.9) and for participants with asthma ruled out, C307.7 (SD C424.1). In the adjusted analyses, a confirmed diagnosis was associated with higher direct healthcare costs (relative ratio (RR)=1.60, 95% CI 1.14 to 2.22), increased rate of specialist visits (RR=2.41, 95% CI 1.05 to 5.40) and reliever medication use (RR=1.62, 95% CI 1.09 to 2.35), but not primary care physician visits (p=0.10) or controller medication use (p=0.11). Conclusions: A quarter of individuals with a physician diagnosis of asthma did not have asthma after objective re-evaluation. These participants still consumed a significant amount of asthma-related healthcare resources. The population-level economic burden of asthma overdiagnosis could be substantial.